STUDY OF THE PHYTOSANITARY STATE OF LANDSCAPE AND FOREST TREES IN ZOMIN AND BAKHMAL FOREST FACILITIES - Nafasov Zafar; Allayarov Nodirjon; Muminov Mansur (Web of Journals Publishing, 2025)
Phytosanitary inspections conduct in the Zomin and Bakhmal forest areas of Jizzakh region. Observations conduct to study the sanitary, entomological and phytopathological condition of all types of ornamental and forest trees and shrubs in the. “Zomin” National Nature Park, Zomin State Forestry and Zomin State Reserve in the Zomin district, as well as the natural conditions of plants, natural reproduction processes, and the incidence of pests and diseases. During the study, the phytosanitary condition of ornamental and forest trees (juniper, pine, poplar, hawthorn, walnut, white birch, almond and fir) in the Usmanlisoy and Suffa areas of the Zomin National Nature Park of Jizzakh region, and the Usmanlisoy and Ariklisoy areas of the Zomin Forestry study.